Comparison of Closed Interlocking Nail Shaft of Femur Versus open Interlocking Nail in Femoral Fracture Treatment - Muhammad Inam, Imran Khan, Hafiz Tayyab Irshad (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Femoral shaft fractures are common traumatic injuries requiring surgical intervention. The choice of surgical technique is critical for optimal patient outcomes. Closed interlocking nailing (CLIN) and open interlocking nailing (OLIN) are both effective methods for femoral shaft fracture fixation. This study compares the clinical outcomes, complication rates, and functional recovery between these two approaches. Methods: A total of 120 patients with femoral shaft fractures were enrolled in this retrospective study. Patients were divided into two groups: 60 underwent CLIN and 60 underwent OLIN. Clinical outcomes, including fracture healing time, complication rates, and functional recovery, were compared. Results: The average time for fracture union was 14.3 weeks in the CLIN group and 13.7 weeks in the OLIN group. Complication rates, including infection and malunion, were slightly higher in the OLIN group. Functional recovery, measured using the Harris Hip Score (HHS), was comparable between both groups. Conclusion: Both closed and open interlocking nailing techniques offer similar outcomes for femoral shaft fractures, but CLIN presents fewer complications and is associated with faster rehabilitation times. Keywords: Femoral fractures, closed interlocking nailing, open interlocking nailing, fracture fixation, complication rates, functional recovery.